DESIGN OF TOURISM BUS RENTAL SYSTEM AT PT. BAGINDO WEB-BASED TRANSWISATA - Daniel Aldani; Agus Sutardjo (Jurnal Manajemen Teknologi Informatika, 2024)
For businesses engaged in transportation services, a rental system is very important. A computerized system is needed to improve the efficiency and productivity of the rental system and ensure the availability of adequate human resources. PT. Bagindo Transwisata does not have a system that can handle all rental activities. The design of an effective and efficient tourist bus rental information system is needed because the process of recording and processing tourist bus rental data is still carried out using records in books and of course there is still the possibility of human error. System modeling is depicted visually through the use of UML (Unified Modeling Language), which is then implemented with the Hypertext Preprocessor (PHP) programming language, with MySQL as the database used. This tourist bus rental information system is expected to help customers make transactions and help the administration and management departments create accurate rental reports. This will encourage effective and efficient performance and help make decision-making plans..